Land Gastropods along an altitudinal gradient on the coast of São Paulo, Brazil - Anjos, Natan Gonçalo dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Environmental factors affect how species are scattered across the globe. Rapoport’s rule states that a greater number of species are found near the Equator, diminishing in direction to the Poles, and the same can be said, from a lower altitude, to a higher one. Land gastropods are the animal group with the highest extinction rate, and one of the groups that can fit under this rule. The land gastropods of Serra do Mar, covered by the Atlantic Rainforest, are understudied; this work seeks to describe the land gastropod communities of two protected areas (Parque Estadual da Serra do Mar and Parque Natural Municipal Nascentes de Paranapiacaba), and to know if they follow altitudinal Rapoport’s rule. We sampled at four points in different altitudes, two on each area. We collected leaf litter and did active search of shells and living individuals. We calculated α-diversity, evenness and β-diversity indices. We found 1559 individuals of 40 species; there was not much change in species richness with altitude, changes in α-diversity also did not change with altitude. β-diversity was mainly explained by species turnover. The land gastropod communities of Parque Estadual da Serra do Mar and Parque Natural Municipal Nascentes de Paranapiacaba do not follow altitudinal Rapoport’s rule.

Fatores ambientais afetam como as espécies se espalham pelo globo. A regra de Rapoport dita que um maior número de espécies é encontrado próximo ao Equador, diminuindo em direção aos polos, e o mesmo pode ser dito, de uma altitude menor, para uma maior. Gastrópodes terrestres são o grupo animal com a maior taxa de extinção, e um dos grupos que podem seguir esta regra. Os gastrópodes terrestres da Serra do Mar, coberta pela Floresta Atlântica, são subestudados; este trabalho busca descrever as comunidades de gastrópodes terrestres de duas áreas protegidas (Parque Estadual da Serra do Mar e Parque Natural Municipal Nascentes de Paranapiacaba) e saber se eles seguem a regra de Rapoport altitudinal. Amostramos quatro pontos em diferentes altitudes, duas em cada área. Coletamos serapilheira e fizemos busca ativa de conchas e indivíduos vivos. Calculamos índices de diversidade α e β, e de equitabilidade. Nós encontramos 1559 indivíduos de 40 espécies; não houve muita mudança de riqueza de espécies em relação à altitude. A diversidade β foi principalmente explicada pelo turnover de espécies. As comunidades de gastrópodes terrestres do Parque Estadual da Serra do Mar e do Parque Natural Municipal Nascentes de Paranapiacaba não seguem a regra de Rapoport altitudinal.
Gastrópodes terrestres ao longo de um gradiente altitudinal na costa de São Paulo, Brasil
Keywords: Diversity; Ecology; Communities; Land snail; Atlantic Rainforest; Gastrópodes; Diversidade biológica; Ecologia; Comunidades; Mata Atlântica; Parque Estadual da Serra do Mar (SP); Paranapiacaba (SP)